A Pareto-based multi-objective optimization algorithm to design energy-efficient shading devices - Khoroshiltseva, Marina; Slanzi, Debora; Poli, Irene (Applied energy, 2016)
•We present a multi-objective optimization algorithm for shading design.•We combine Harmony search and Pareto-based procedures.•Thermal and daylighting performances of external shading were considered.•We applied the optimization process to a residential social housing in Madrid. In this paper we address the problem of designing new energy-efficient static daylight devices that will surround the external windows of a residential building in Madrid. Shading devices can in fact largely influence solar gains in a building and improve thermal and lighting comforts by selectively intercepting the solar radiation and by reducing the undesirable glare. A proper shading device can therefore significantly increase the thermal performance of a building by reducing its energy demand in different climate conditions. In order to identify the set of optimal shading devices that allow a low energy consumption of the dwelling while maintaining high levels of thermal and lighting comfort for the inhabitants we derive a multi-objective optimization methodology based on Harmony Search and Pareto front approaches. The results show that the multi-objective approach here proposed is an effective procedure in designing energy efficient shading devices when a large set of conflicting objectives characterizes the performance of the proposed solutions.